Study of Brazilian commercial Oriented Strand Board panels using stress wave - Morales, Elen Aparecida Martines [UNESP]; Da Silva Bertolini, Marília; Do Nascimento, Maria Fátima; Lahr, Francisco Antonio Rocco; Ballarin, Adriano Wagner [UNESP] (My University, 2013)
Today lumber industry has shown a clearly evident trend towards wood based panels' production; and, among them, Oriented Strand Board (OSB) has become more and more prominent. Nondestructive Testing (NDT) such as stress wave is one of the possible ways to make their mechanical characterization. This study aimed to investigate the efficiency of NDT stress wave to estimate mechanical parameters of Brazilian commercial OSB panels. National commercial OSB panels (15 and 25 mm in thickness) were tested by standard methods, EN codes, and non-destructive tests employing Stress Wave Timer, METRIGUARD, model 239 A. Data obtained in tests were analyzed using mean comparison by analysis of variance (ANOVA) and Tukey method. R2 values greater than those established by EN 326-2 2002 to determine correlation between mechanical properties in bending (f m and Em), obtained by the standard and non-destructive testing, suggest the possibility of using stress wave for quality control in OSB industry.
Keywords: Nondestructive Testing; Oriented Strand Board; Static mechanical properties; Stress wave; Mechanical characterizations; Mechanical parameters; Non destructive testing; Non-destructive test; Oriented Strandboard; Wood-based panels; Mechanical properties; Nondestructive examination; Elastic waves